Posisi kitab al-Muwatta dalam sejarah hukum Islam: analisis atas pandangan Yasin Dutton - Noorhidayati, Salamah (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
This article discusses an academic discourse on the origin of Islamic Law by describing third school between two schools existing in this controversial field. By descriptive and comparative method, this article tries to describe how Yasin Dutton views on the beginning of Islamic Lawâs construction, and then how he digs his hypothesis against two dominant schools involved in the discussion of the date of Islamic Law birth. Dutton finds that if the Qurâan is the first written formulation of Islam in general, al-Muwatta of Malik is arguably the first written formulation of the Islam-in-practiceâ that becomes Islamic law. This way is missing in the first and second school attention. He considers the methods used by Malik in the Muwattaâ to derive the judgements of the law from the Qurâan is thus concerned on one level with the finer details of Qurâanic interpretation. However, since any discussion of the Qurâan in this context must also include considerations of the other main source of Islamic law, namely the sunna, or normative practice of the Prophet, this latter concept, especially its relationship to the terms of hadith and amal (traditionsâ and living traditionâ), also receives considerable attention. it is impossible, for Dutton, to find that these two main legitimate sources, textual and practical, will be different and in dispute. This third school wanted to fill the gap between these two schools using different object and argument although in someway meet in same conclusion.